2016
DOI: 10.1002/brb3.602
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant neural networks for the recognition memory of socially relevant information in patients with schizophrenia

Abstract: IntroductionPatients with schizophrenia exhibit several cognitive deficits, including memory impairment. Problems with recognition memory can hinder socially adaptive behavior. Previous investigations have suggested that altered activation of the frontotemporal area plays an important role in recognition memory impairment. However, the cerebral networks related to these deficits are not known. The aim of this study was to elucidate the brain networks required for recognizing socially relevant information in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Finally, 19 components were identified as functional networks or subnetworks. Similar networks were used in our previous study (Oh et al, 2017 ). Figure 2 depicts some of the 19 selected components; they represent the well-known resting state functional networks: the default mode network, sensorimotor network, visual network, and frontal network.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 19 components were identified as functional networks or subnetworks. Similar networks were used in our previous study (Oh et al, 2017 ). Figure 2 depicts some of the 19 selected components; they represent the well-known resting state functional networks: the default mode network, sensorimotor network, visual network, and frontal network.…”
Section: Methodsmentioning
confidence: 99%
“…This disorder can cause chronic impairments in cognition, perception, reality testing, and emotion among others (Bhugra, 2005 ). Its underlying mechanism is still unclear, even though it is considered to involve structural and functional brain abnormalities (Ho et al, 2003 ; Karlsgodt et al, 2010 ; Oh et al, 2015 , 2017 ). Schizophrenia is usually diagnosed on the basis of history and mental status examination by psychiatrists under the guidelines of specified diagnostic criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Schizophrenia is a severe psychiatric disorder, characterized by delusions, hallucinations and disorganized thinking (Hu et al, ), which affects about 1% of the world's population (Dhindsa & Goldstein, ; Lieberman, Scott Stroup, & Perkins, ; Nowak, Sabariego, Switaj, & Anczewska, ; Rajji, Miranda, & Mulsant, ). Its etiology and neuropathology are not well understood, even though neuroimaging studies have revealed distributed structural and functional brain abnormalities (Karlsgodt, Sun, & Cannon, ; Oh et al, ; Oh et al, ). Schizophrenia is usually diagnosed by a clinical examination carried out by psychiatrists.…”
Section: Introductionmentioning
confidence: 99%
“…Each dataset comprised high‐resolution T1‐weighted images and rs‐fMRI, allowing us to examine classification accuracy for each modality as well as their integration. Because schizophrenia is considered to involve structural as well as functional brain abnormalities (Karlsgodt et al, ; Oh et al, ; Oh et al, ), we hypothesized that (a) both structural and functional data would allow single‐subject classification with statistically significant accuracy. In addition, given the existing evidence for both regional and network‐level alterations in schizophrenia (Y. Liu et al, ; Micheloyannis et al, ; Shen, Wang, Liu, & Hu, ), we hypothesized that, within each modality, (b) the combination of voxel‐wise images and connectome‐wide based matrices would be superior to the use of either voxel‐wise images or connectome‐wide based matrices by themselves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation